2018
DOI: 10.1029/2018gl077993
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gravity Wave Drag Optimization in the Splitting of the Antarctic Vortex in the 2002 Sudden Stratospheric Warming

Abstract: The impact of gravity wave drag on the Antarctic sudden stratospheric warming (SSW) in 2002 is examined through a mechanistic middle atmosphere model combined with a variational data assimilation system. Significant differences in the SSW representation are found between a model integration that uses reference gravity wave parameters and one that uses parameters estimated using data assimilation. Upon identical wave forcings at 100 hPa, the vortex breakdown may arise as either a vortex splitting event or a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…GWs exhibit a large spatial and temporal variability, which is closely linked to the synoptic conditions, the propagation conditions and the source of the GWs. Thus, there is a huge variability in the global GW distribution (Ern et al, 2004;Fröhlich et al, 2007;Hoffmann et al, 2013;Schmidt et al, 2016). Most of the regions of enhanced GW activity are connected to (i) orography (Hoffmann et al, 2013), which is quite stable and persistent in space and time, or (ii) deep convection (in the Tropics; Ern and Preusse, 2012) as well as to jet sources (mainly in the midlatitudes; Plougonven and Zhang, 2014), which are spatially and temporally variable.…”
Section: Introductionmentioning
confidence: 99%
“…GWs exhibit a large spatial and temporal variability, which is closely linked to the synoptic conditions, the propagation conditions and the source of the GWs. Thus, there is a huge variability in the global GW distribution (Ern et al, 2004;Fröhlich et al, 2007;Hoffmann et al, 2013;Schmidt et al, 2016). Most of the regions of enhanced GW activity are connected to (i) orography (Hoffmann et al, 2013), which is quite stable and persistent in space and time, or (ii) deep convection (in the Tropics; Ern and Preusse, 2012) as well as to jet sources (mainly in the midlatitudes; Plougonven and Zhang, 2014), which are spatially and temporally variable.…”
Section: Introductionmentioning
confidence: 99%
“…Model experiments already showed that changes in GW parameters, e.g. the GW drag or the momentum flux, which modify the polar vortex geometry or even the stability (Samtleben et al, 2019), can lead to different kinds of vortex breakdowns (splitting or displacement) in connection with PW activity (Šácha et al, 2016;Scheffler et al, 2018). As a result, the vortex geometry 2 https://doi.org/10.5194/angeo-2019-120 Preprint.…”
Section: Introductionmentioning
confidence: 99%
“…CC BY 4.0 License. including a weakening or strengthening of the vortex itself strongly depends on the temporal and spatial GW drag distribution (Scheffler et al, 2018;Samtleben et al, 2019). These approaches provide a new basis regarding the evaluation of SSW events, which are strongly affected by GWs as well as by PWs.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the favourable case where a model bias has been convincingly shown to be tied to missing gravity wave drag (McLandress et al ., ), there are several different changes possible to gravity wave parameterizations that will alleviate this bias (Choi and Chun, ; de la Cámara et al ., ; Garcia et al ., ). Stratospheric variability, even in models with relatively fine spatial resolution, remains sensitive to non‐orographic gravity wave parameterizations (Polichtchouk et al ., ; Scheffler et al ., ), making these a key component for tuning.…”
Section: Constraining Gravity Wave Sources In Parameterizationsmentioning
confidence: 99%